Non-Economic Quality of Life and Population Density in South Africa - Talita Greyling; Stephanié Rossouw (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2016)
The main purpose of this study is to investigate the relationship between population density and non-economic quality of life. Popular opinion has generally been that population density can be seen as beneficial for economic growth, as it allows for greater productivity, greater incomes and can be translated into higher levels of quality of life. Recently though, growing evidence tends to suggest the exact opposite in that increases in productivity and incomes are not translated into better quality of life. As economic or income variables have always played a significant role in any research, questions regarding the relationship between population density and non-economic quality of life has largely remained unanswered. In this light, the paper utilises a panel data set on the eight metropolitans in South Africa for the period 1996 to 2014 to determine the relationship between population density and non-economic quality of life in the South African context. In the analyses we make use of panel estimation techniques which allows us to compare changes in this relationship over time as well as adding a spatial dimension to the results. This paper contributes to the literature by firstly studying the aforementioned relationship over time and secondly conducting the analyses at a sub-national basis in a developing country. Our results show that there is a significant and negative relationship between population density and non-economic quality of life. Based on our findings policy measures to encourage urbanisation should not be supported if the ultimate outcome is to increase non-economic quality of life.
Keywords: O15; O18; O55; R11; R00; C01; C33; C43; 330; Quality of life; Population density; Urbanisation; South Africa; Panel data analysis